On the Convergence of Projector-Splines for the Numerical Evaluation of Certain Two-Dimensional CPV Integrals (Journal of Computational Mathematics, 2002)
In this paper, product formulas based on projector-splines for the numerical evaluation of 2-D CPV integrals are proposed. Convergence results are proved, numerical examples and comparisons are given.